Introduction to logic - Copi, Irving M. 4 0 16; 1931- Cohen, Carl; 5 (Upper Saddle River, NJ : Prentice Hall, 1998)
Explains the basic principles and techniques used in the study of logic, with emphasis on reasoning, language, deduction, and induction; and includes the Logic Review program on CD-ROM.
Includes indexes.
Adult;Adult.
System requirements for accompanying disc: 8088 or higher processor; 512K memory or greater; DOS 2.0 or higher, or Windows 3.x or higher; CD-ROM drive.
Keywords: 2 -- 0; 6; Logic.;Logic.; 20; 2